Intimate Partner Violence from Schema Therapy Perspective - Ayse Gokcen Gundogmus; Suheyla Dogan Bulut; Yasir Safak (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Schema Therapy developed by Jeffrey Young is a psychotherapy method used in the treatment of many psychiatric disorders, particularly personality disorders. Early maladaptive schemas, which is one of the fundamental concepts of Schema Therapy, are self-destructive emotional and cognitive patterns that begin in early childhood, develop during childhood/adolescence, and elaborate and repeat throughout lifetime. In literature, studies on schema therapy and partner violence (exposure and perpetration) mostly investigated the mediator role of early maladaptive schemas. Study results support the mediator role of early maladaptive schemas to become victims or perpetrators of violence in the future in people with a childhood abuse/neglect history. Especially, the connection between having the schemas in the domain of disconnection/rejection area and being a victim of violence has been determined. Considering that personality traits are more frequently detected in cases of domestic violence, the use of schema therapy, which integrates many therapeutic techniques into a therapy model (especially in a problematic area with multi-faceted manner such as violence), is promising even though there are few studies on the effectiveness of schema therapies in couples. In this review article, we will first give information about the concepts of schema therapy and then review the related studies on relationship between domestic violence/perpetration and early maladaptive schemas. Finally, we will give information about the approach to domestic violence using schema therapy in intimate partners. [JCBPR 2019; 8(2.000): 117-127]